Coupled-plasma filtration and adsorption for severe burn patients with septic shock and acute kidney injury treated with renal replacement therapy. Issue 1 (February 2020) - Mariano, Filippo; Hollo', Zsuzsanna; Depetris, Nadia; Malvasio, Valeria; Mella, Alberto; Bergamo, Daniela; Pensa, Anna; Berardino, Maurizio; Stella, Maurizio; Biancone, Luigi
Highlights: Prognosis is poor for AKI patients requiring renal replacement therapy with septic shock sustained by polyresistant strains. Treatment by coupled-plasma filtration adsorption improved mortality predicted by Baux score mortality. SOFA score was the only significant predictor of mortality. The trend of outcome was statistically non-significant better with regional citrate anticoagulation than with heparin. Abstract: Background: Coupled-plasma filtration adsorption (CPFA) is a sorbent-based technology aimed at removing soluble mediators of septic shock. We present our experience on the use of CPFA in septic shock severe burn patients with acute kidney injury (AKI) needing renal replacement therapy (RRT) with the main goal to evaluate efficacy and safety of CPFA in this specific subset of septic shock patients. Methods: In this observational study, we retrospectively reviewed the medical notes of all burn patients admitted to our adult Burn Center who received CPFA, as part of the septic shock treatment requiring RRT, between January 2001 and December 2017 (CPFA group). We compared CPFA group with all the burn patients admitted to our Center in the same period of time, with the same range of relevant clinical characteristics, who developed AKI and were treated with RRT, but not CPFA (control group). We collected demographic characteristics, burn size, Sequential Organ Assessment Failure (SOFA) score, microbiological data, and patient outcome, in terms of in-hospital mortality rate and the probability of survival calculated using the revised Baux score. We also collected data regarding CPFA safety (hemorrhagic episodes, catheter associated-complications, hypersensitivity reactions) and efficiency (number and duration of CPFA sessions, plasma treated amount, plasma processed dose). Results: 39 severe burn patients were treated with CPFA (CPFA group) (mean age 46.0 years, range 40.0–56.0 years; mean burn size 48.0% TBSA, range 35.0–60.0% TBSA), and 87 patients treated with RRT, but not CPFA, who had similar clinical characteristics (control group). Observed mortality rate was 51.3% in the CPFA group and 77.1% in the control group (p 0.004). Regarding factors affecting survival in the CPFA group, SOFA score on the 1st day of CPFA resulted significant (OR 2.016, 95% CI, 1.221–3.326; p < 0.004) in the multivariate analysis logistic model. Conclusions: CPFA treatment for burn patients with AKI-RRT and septic shock, sustained by bacterial strains non or poorly responsive to therapy, was associated with a lower mortality rate, compared to RRT alone. However, further research, such as large prospective studies, is required to clarify the role of CPFA in the treatment of burns with septic shock and AKI-RRT.